2013
DOI: 10.1038/ki.2013.97
|View full text |Cite
|
Sign up to set email alerts
|

Signal regulatory protein-α interacts with the insulin receptor contributing to muscle wasting in chronic kidney disease

Abstract: Insulin resistance from chronic kidney disease (CKD) stimulates muscle protein wasting but mechanisms causing this resistance are controversial. To help resolve this, we used microarray analyses to identify initiators of insulin resistance in the muscles of mice with CKD, glucose intolerance and insulin resistance. CKD raised mRNAs of inflammatory cytokines in muscles and there was a 5.2-fold increase in signal regulatory protein-α (SIRP-α), a transmembrane glycoprotein principally present in muscle membranes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 38 publications
4
56
0
Order By: Relevance
“…Our previous studies proved that IGF-1 plays a central role in controlling the muscle wasting of CKD. 5,[24][25][26] In this study, we found that LFES upregulates local IGF-1 and thus, provides a means of increasing muscle mass and function. There are four lines of evidence supporting this conclusion.…”
Section: Discussionmentioning
confidence: 81%
“…Our previous studies proved that IGF-1 plays a central role in controlling the muscle wasting of CKD. 5,[24][25][26] In this study, we found that LFES upregulates local IGF-1 and thus, provides a means of increasing muscle mass and function. There are four lines of evidence supporting this conclusion.…”
Section: Discussionmentioning
confidence: 81%
“…Reddy et al concluded that a high SUN not only increased reactive oxygen species but also caused insulin resistance (96). However, it is difficult to assign insulin resistance to a single factor considering that there are so many uremia-induced complex metabolic pathways (97,98). It will be interesting to evaluate whether the production of Another potential role of urea in producing uremiainduced toxicity is through the development of protein carbamylation, which could disrupt the structure of a protein interfering with signaling pathways and so forth.…”
Section: Is Urea Toxic?mentioning
confidence: 99%
“…42 The cells were treated with a cytokine mixture of IL-6 (2 ng/ml), TNF-a (2 ng/ml), and TGF-b1 (2 ng/ml). 4 Mechanical Stretch C2C12 cells were plated on silicone elastomer-bottomed plates and subjected to mechanical stretch as described. 33 Briefly, at 90% confluence, cells were exposed to a cyclic mechanical stretch with a computercontrolled mechanical Strain Unit (Flexcell 4000) set at cyclic (60 cycles per minute) stretch.…”
Section: Exercise Trainingmentioning
confidence: 99%
“…The degradation of insulin-receptor substrate 1 impairs activities of phosphatidylinositol 3-kinase (PI3K) and the Akt. 4 The reduced phosphorylation of these signaling proteins results in decreased phosphorylation of forkhead transcription factors (FoxOs) with activation of caspase-3 and expression of the ubiquitin E3 ligases, Atrogin1 and MuRF1. The result is stimulation of muscle protein degradation.…”
mentioning
confidence: 99%